Maternal Zika Virus Disease Severity, Virus Load, Prior Dengue Antibodies, and Their Relationship to Birth Outcomes. (23rd May 2017) - Halai, Umme-Aiman; Nielsen-Saines, Karin; Moreira, Maria Lopes; de Sequeira, Patricia Carvalho; Junior, Jose Paulo Pereira; de Araujo Zin, Andrea; Cherry, James; Gabaglia, Claudia Raja; Gaw, Stephanie L; Adachi, Kristina; Tsui, Irena; Pilotto, Jose Henrique; et al.
Summary: Maternal Zika symptom severity or ZIKA-RNA load at time of infection did not impact birth outcomes in our cohort analysis. Presence of prior maternal dengue antibodies had no effect on Zika infection severity, RNA load, or birth outcomes. Abstract: Background: Congenital Zika virus (ZIKV) syndrome is a newly identified condition resulting from infection during pregnancy. We analyzed outcome data from a mother-infant cohort in Rio de Janeiro in order to assess whether clinical severity of maternal ZIKV infection was associated with maternal virus load, prior dengue antibodies, or abnormal pregnancy/infant outcomes. Methods: A clinical severity assessment tool was developed based on duration of fever, severity of rash, multisystem involvement, and duration of symptoms during ZIKV infection. ZIKV-RNA load was quantified by polymerase chain reaction (PCR) cycles in blood/ urine. Dengue immunoglobulin G (IgG) antibodies were measured at baseline. Adverse outcomes were defined as fetal loss or a live infant with grossly abnormal clinical or brain imaging findings. Regression models were used to study potential associations. Results: 131 ZIKV-PCR positive pregnant women were scored for clinical disease severity, 6 (4.6%) had mild disease, 98 (74.8%) had moderate disease, and 27 (20.6%) severe manifestations of ZIKV infection. There were 58 (46.4%) abnormal outcomes with 9 fetal losses (7.2%) in 125 pregnancies. No associations were found between: disease severity and abnormal outcomes ( P = .961; odds ratio [OR]: 1.00; 95% confidence interval [CI]: 0.796–1.270); disease severity and viral load ( P = .994); viral load and adverse outcomes ( P = .667; OR: 1.02; 95% CI: 0.922–1.135); or existence of prior dengue antibodies (88% subjects) with severity score, ZIKV-RNA load or adverse outcomes ( P = .667; OR: 0.78; 95% CI: 0.255–2.397). Conclusions: Congenital ZIKV syndrome does not appear to be associated with maternal disease severity, ZIKV-RNA load at time of infection or existence of prior dengue antibodies.